2021
DOI: 10.1016/j.genrep.2020.101012
|View full text |Cite
|
Sign up to set email alerts
|

Computationally predicted SARS-COV-2 encoded microRNAs target NFKB, JAK/STAT and TGFB signaling pathways

Abstract: Recently an outbreak that emerged in Wuhan, China in December 2019, spread to the whole world in a short time and killed >1,410,000 people. It was determined that a new type of beta coronavirus called severe acute respiratory disease coronavirus type 2 (SARS-CoV-2) was causative agent of this outbreak and the disease caused by the virus was named as coronavirus disease 19 (COVID19). Despite the information obtained from the viral genome structure, many aspects of the virus-host interactions during infection is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 75 publications
1
83
0
Order By: Relevance
“…The increase in IL-6 observed in severe COVID-19 patients is associated with significantly lower survival rates (6,96). COVID-19 patients present both dysregulated JAK/STAT pathway ( 97) and important role of TGF-b/Smad pathway (98).…”
Section: Wnt/b-catenin Pathway and Sars-cov-2 Infectionmentioning
confidence: 99%
“…The increase in IL-6 observed in severe COVID-19 patients is associated with significantly lower survival rates (6,96). COVID-19 patients present both dysregulated JAK/STAT pathway ( 97) and important role of TGF-b/Smad pathway (98).…”
Section: Wnt/b-catenin Pathway and Sars-cov-2 Infectionmentioning
confidence: 99%
“…In addition to MRE/GRE and SP1-binding sites, the Na,K-ATPase β 1 -subunit contains prostaglandin-, hypoxia-, thyroid-, calcium-, and serum-response elements ( 44 ). Of note, it has been previously demonstrated that both SARS-CoV and SARS-CoV-2 alter the activity of AP-1 ( 45 , 46 ) and SP1 transcriptional pathways ( 47 ). Moreover, two recent publications demonstrated that infection of various lung epithelial cells with SARS-CoV-2 leads to decreased expression of the α 1 -, α 2 -, α 3 -, β 1 -, and β 3 -subunits of the Na,K-ATPase at the transcriptional level ( 48 , 49 ).…”
Section: Direct Effects Of Sars-cov-2 Infection On Expression Maturation and Trafficking Of Nak-atpase In Infected Cellsmentioning
confidence: 99%
“…This study further demonstrates that sv-RNA molecules derived from viral nucleoprotein and non-structural protein 3 regions contribute to SARS-CoV pathogenesis, which is reduced by antagonization of these sv-RNAs ( Morales et al, 2017 ). Another bioinformatics-driven prediction study revealed that SARS-CoV-2 encodes multiple putative rv-miRNAs from different regions of the viral genome and targets various signaling molecules involved in apoptosis, immune function, cell cycle, and transcription ( Aydemir et al, 2021 ). However, further investigations are required to experimentally evaluate their expression and biological functions in the context of viral infection.…”
Section: Rna Virus-encoded Mirnas (Rv-mirnas)mentioning
confidence: 99%